Realidade virtual e jogos com Kinect como recurso didático interdisciplinar no ensino-aprendizagem: uma analise da utilização no ensino de ciências naturais e inglês no ensino médio em Macapá - MESQUITA, Adrian Souza (Instituto Federal do Amapá, 2021)
Technology has been increasingly used in our daily lives, at work, in health and in several other areas, in education, it is not different over the years. the educational area has evolved considerably in the area of technology, one of the advances that can to be addressed is the virtual reality and Kinect games that have been innovating teaching learning, this work aims to put into practice activities and analyze educational games that help students in natural science subjects and also in a better understanding of the English language, using these tools, we will be able to analyze students' interactions with games and activities, thus qualifying the impact that these tools have on teaching and learning of high school classes in Macapá.